2017
DOI: 10.1002/gch2.201700063
|View full text |Cite
|
Sign up to set email alerts
|

Eco‐Friendly and High Performance Supercapacitors for Elevated Temperature Applications Using Recycled Tea Leaves

Abstract: energy supply are required. Hence, an efficient local energy storage/production system plays a vital role for such applications. [1] The supercapacitor is one of the efficient energy storage systems which can store energy via electric double layer and faradic reactions. [2,3] The electric double layer capacitor (EDLC) stores the charge over the active surface area of the material and shows very durable performance over long period. [3,4] Thus, creating carbon with a high surface area could be one of the ways t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 73 publications
(36 citation statements)
references
References 63 publications
3
33
0
Order By: Relevance
“…This could be due to increased nitrogen content within the carbon resulting in improved graphitic structure even after activation, as observed in previous reports [11,26]. The graphitization ratio of CP-NA was much higher than that of previously reported N, P co-doped activated coffee and ZnCl 2 activated coffee shell samples [9,10].…”
Section: Resultssupporting
confidence: 58%
See 1 more Smart Citation
“…This could be due to increased nitrogen content within the carbon resulting in improved graphitic structure even after activation, as observed in previous reports [11,26]. The graphitization ratio of CP-NA was much higher than that of previously reported N, P co-doped activated coffee and ZnCl 2 activated coffee shell samples [9,10].…”
Section: Resultssupporting
confidence: 58%
“…Phosphorous and nitrogen co-doped activated carbon from spent coffee grounds was synthesized using ammonium polyphosphate via microwave-assisted synthesis [10]. In our previous studies, we have reported facile production of bio-waste-derived activated carbons using KOH activation, for supercapacitor applications [11][12][13][14][15][16]. Utilizing the KOH activation technique, we have demonstrated varied pore size distribution, control over the surface area of activated carbons and a resulting promising charge storage performance of the device.…”
Section: Introductionmentioning
confidence: 99%
“…Higher specific capacitance values were observed with decreasing scan rates. A similar behavior was observed in other reports of energy storage systems [28,[42][43][44]. The CV curves of CoFe 2 O 4 ED@NF in 3M KOH electrolyte at various scan rates are given in Figure S7a.…”
Section: Resultssupporting
confidence: 86%
“…This could be the result of sufficient time provided for redox reactions at low current densities. Redox reactions promoted at low current densities lead to better charge storage compared with other non-faradic systems [43][44][45][46]. At a current density of 0.5 A/g, a high specific capacitance of 768 F/g was observed.…”
Section: Resultsmentioning
confidence: 92%
“…Comparison of Raman spectra for foams with 0%, 1%, and 2% phosphorus can be observed from Figure . Phosphorus‐containing burnt foams showed two peaks around 1350 and 1560 cm −1 representing diamond and graphitic phase of carbon, respectively . Ratio of intensities of diamond ( I d ) and graphitic phase ( I g ) determines the structure of char.…”
Section: Resultsmentioning
confidence: 99%